Helminth Parasites of Pigs and Development of Suitable Strategy for Its Control - Baskota, N.; Shrestha, S. P. (Nepalese Veterinary Journal, 2019)
The study aimed to formulate the suitable development strategies to control helminthiasis in pig by understanding the nature of the epidemiological pattern that is yet to exploit to further enhance its productivity. A longitudinal study was done to find the general prevalence pattern of helminth parasites from June/ July 2017 to May/June 2018 in the research farm of Swine and Avian Research Program, Khumaltar. A total of 50 animals of different age groups were considered for the study and they were deprived of antihelminthic treatment throughout the study period. The fecal samples were collected at 3-4 months interval and EPG was done as per the standard protocol. Three different groups of antihelminthic were used including a control group as different treatments and they were assigned as T1- Pyrantel pamoate, T2- Benzimidazoles, T-3 Imidazothiazole, and T-4 Control. The EPG was done for at least 3-week post-treatment. The result of this study showed the significant effect of the season (p<0.05) as a high prevalence of roundworms especially Ascaris (60%) and Strongylus (40%) during June/ July with more than 30 cases. However, a slight increase in parasitic prevalence was seen in September/October and Jan/Feb too. Similarly, all the antihelminthics used were 100% effective (p>0.05) against these roundworms. The female and young groups of animals showed remarkable symptoms of parasitic infections compared to the male ones. In conclusion, the different groups of drugs demonstrated very satisfactory performances in terms of the removal of parasites for good health of pigs and these should be given at 3-4 months interval as routine deworming schedule.